2019
DOI: 10.4314/bajopas.v11i1.65s
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae and sustainable wastewater treatment: a Review

Abstract: Microalgae play important roles in the realisation of energy wastewater treatment. This is achievable through coupling carbon capture with wastewater treatment and consequent biomass production. Unlike activated sludge, microalgal is more of a resource than a waste. This paper presents a review on the use of microalgae in sustainable wastewater treatment including organic matter, nitrogen, phosphorus and heavy metals removal. The paper also focussed on microalgal cultivation potentials of using microalgal phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Microalgae are widely employed in bioremediation processes due to their even distribution, high tolerance to environmental conditions [1] as well as their modes of nutrition and metabolic activities [2]. Algae can easily grow in the presence of moisture thereby utilizing the available energy from light to photosynthesize [3] and increase in concentration within a short period of time [4], accumulate pollutants through the cell surface [5] and absorb positively charged heavy metal ions present in the wastewater stream to their cell walls by anionic ligands [6,7]. Several types of research reported the extraction of energy molecules from algal biomass that range from bioethanol, biodiesel, biogas, biohydrogen, methane and many other valuable energy alternatives [1,8,9] that make algal bioremediation more attractive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae are widely employed in bioremediation processes due to their even distribution, high tolerance to environmental conditions [1] as well as their modes of nutrition and metabolic activities [2]. Algae can easily grow in the presence of moisture thereby utilizing the available energy from light to photosynthesize [3] and increase in concentration within a short period of time [4], accumulate pollutants through the cell surface [5] and absorb positively charged heavy metal ions present in the wastewater stream to their cell walls by anionic ligands [6,7]. Several types of research reported the extraction of energy molecules from algal biomass that range from bioethanol, biodiesel, biogas, biohydrogen, methane and many other valuable energy alternatives [1,8,9] that make algal bioremediation more attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies highlighted some ways to minimising the production cost of algal biomass extracts as [2] suggest that mass cultivation of microalgae may reduce the production cost and will also increase the quantity of valuable energy molecules extractions. [5,[10][11][12] indicated increased treatment efficiencies and microbial biodegradability when activated sludge was incorporated into the microalgal treatment due to symbiotic relationship that exist between algae and bacteria by production of oxygen as by-product of photosynthesis which was needed by bacterial cells for waste degradation. Also production of carbon-dioxide as a result of bacterial degradation termed as mineralization by [13], which was cheaply utilized by microalgae in photosynthesis [3].…”
Section: Introductionmentioning
confidence: 99%
“…From the environmental point of view, the utilization of microalgae biomass as alternative green adsorbent to remove pharmaceuticals from water is a biorefinery approach in line with the circular economy principles [37,40,41]. According to these principles, most or all of microalgae potential should be profitably exploited while waste production should be minimized [37].…”
Section: Introductionmentioning
confidence: 99%